PENGUATAN PERAN LEMBAGA SEKOLAH DALAM PENCEGAHAN DAN PENAGGULANGAN HIV DAN AIDS PADA SISWA SLTA DIKAWASAN TRETES PRIGEN PASURUAN MELALUI STUDENT LEARNING CENTER (SLC) - Ahmad Zainuddin; Zainul Ahwan; Mochamad Hasyim (LPPM Universitas Yudharta Pasuruan, 2018)
Official data from the National AIDS Commission [KPA] shows that East Java ranks second [two] national HIV most with 33,043 cases of HIV and AIDS as many as 17,014 cases. Whereas Pasuruan Regency was ranked 2 [two] with the highest number of HIV cases from all districts in East Java with 1212 cases. The majority of HIV cases are dominated by productive age / adolescents / school students between the ages of 20-29 years, the number of which reaches around 345 people or around 24%. of the total HIV cases in Pasuruan Regency which amounted to 1212 cases. [KPA data of Kab. Pasuruan from 2000-2016]. Whereas in terms of HIV data by region, Prigen Subdistrict still ranks first as the region with the most HIV cases in Pasuruan Regency with 93 cases. Seeing this problem, the strengthening of school institutions in the prevention and control of the dangers of HIV and AIDS is a priority to be realized. This community service activity (PKM) uses the Community Organizer (CO) approach which is implemented in 5 (five) high schools in the district. Prigen Pasuruan. The tangible results of this service program have made a real contribution to the establishment of high school education institutions in the Prigen area with the increase in the capacity of teachers and students in the prevention of HIV and AIDS and drugs in both religious and medical studies, making strategies and techniques for the campaign of HIV and Aids and network strengthening formed between educational institutions, AIDS prevention commissions in Kab. Pasuruan, the health office and the college of Yudharta Pasuruan University